A-01 Comparing State Anxiety Between Concussed Athletes with and without a History of Sport Related Concussion. (18th June 2020) - Anderson, M; Zynda, A J; Petit, K M; Tomczyk, C P; Covassin, T
Abstract: Objective: To compare state anxiety between concussed athletes with and without a history of sport related concussion (SRC). Method: This study utilized a cross-sectional design. The State Trait Anxiety Inventory (STAI) was administered to athletes within 72 hours of SRC diagnosis. The STAI is a subjective, 40-item inventory that assesses state and trait anxiety; however, this study only examined the state anxiety component. Participants reported how they were feeling at the moment of testing on a 4-point Likert scale ranging from 1 (not at all) to 4 (very much so). State anxiety scores range from 20–80, with higher scores indicating higher levels of state anxiety. An independent samples t-test was used to compare state anxiety between concussed athletes with and without a history of SRC. Statistical significance was set at p < .05. Results: A total of 104 (18.12 ± 2.5 years; male = 65, female = 39) high school (n = 36) and collegiate (n = 68) athletes completed the STAI within 72 hours of SRC. Fifty-nine (56.7%) concussed athletes had no history of SRC and 45 (43.3%) athletes had a history of one or more SRCs. There was no significant difference in state anxiety between concussed athletes with (37.64 ± 9.22) and without (38.47 ± 9.44) a history of SRC (p = .65). Conclusions: This study suggests that concussion history does not affect state anxiety after SRC. However, clinicians should continue to assess emotional changes after SRC in order to best manage and treat SRC.